2019
DOI: 10.15507/2658-4123.029.201901.008-019
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Optimum Safety Factor Method for Reliability-Based Topology Optimization Applied to Free Vibrated Structures

Abstract: Introduction. The classical topology optimization leads to a prediction of the structural type and overall layout, and gives a rough description of the shape of the outer as well as inner boundaries of the structure. However, the probabilistic topology optimization (or reliability-based topology optimization) model leads to several reliability-based topologies with high performance levels. The objective of this work is to provide an efficient tool to integrate the reliability-based topology optimization model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…After the sample preparation, the axial tension test was carried out at a speed of 50 mm/min and the samples with standard length and dimensions meet international standard specifications [13] for polymer and rubber deformation. In figure 2, the curves obtained reflect the mechanical behavior of rubber specimens as a result of axial tension test.…”
Section: Resultsmentioning
confidence: 99%
“…After the sample preparation, the axial tension test was carried out at a speed of 50 mm/min and the samples with standard length and dimensions meet international standard specifications [13] for polymer and rubber deformation. In figure 2, the curves obtained reflect the mechanical behavior of rubber specimens as a result of axial tension test.…”
Section: Resultsmentioning
confidence: 99%
“…The RBTO can be integrated at the conceptual design stage to sketch several types of hollow stems according to the daily loading cases [17][18][19]. In this section, a 2D model [19] is considered for simplicity to carry out the different topology optimization studies.…”
Section: Total Hip Replacementmentioning
confidence: 99%
“…The RBTO can be integrated at the conceptual design stage to sketch several types of hollow stems according to the daily loading cases [10][11][12]. In this section, a 2D model is considered for simplicity to carry out the different topology optimization studies [12].…”
Section: Integration Of Rbto Into Total Hip Replacementmentioning
confidence: 99%
“…Furthermore, when the RBTO model leads to more reliable structures compared to the DTO model for the same weight levels [1]. Two points of view are presented for the RBTO developments: topology optimization [2][3][4] and reliability analysis [5,6]. Considering previous works, it has been shown that the point of view 'topology optimization' seems to be interesting for structural designers since it provides several reliability-based structures relative the reliability index changes.…”
Section: Introductionmentioning
confidence: 99%